ALZHEIMER'S AND CURRENT THERAPEUTICS: A REVIEW - Panche, Archana; Chandra, Sheela; DIWAN AD; Harke, Sanjay (Asian Journal of Pharmaceutical and Clinical Research, 2015)
In recent past several efforts have been made to analyze the symptoms, causes, and cure of Alzheimer's disease (AD) and also to reveal biochemical changes and pathogenesis of the brain affected with AD. Several studies indicated the main cause of the disease is deposition of necrotic Î²-amyloid plaques in the brain. The enzymes Î²-secretase and Î³-secretase catalyze the Î²-amyloid production. It has also been observed that the cells producing acetylcholine, a major neurotransmitter, are destroyed by two closely related enzymes namely acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) in AD progression leading to cognitive disabilities. Hence, the research is going on in finding the inhibitors for these enzymes which will help to either prolong or cure the AD. Discovering the inhibitors for AChE and BChE without side effects remains a major challenge as the AChE and BChE inhibiting drugs available possess several side effects. Several new drugs are being discovered utilizing medicinal plant resources. Uses of flavonoids as plant secondary metabolites are being tried for the treatment of AD. Efforts are being made to apply computational knowledge to streamline the drug discovery process. Nevertheless, blood-brain barrier (BBB) permeation plays a vital role in drug discovery. BBB a physical barrier in the brain through which the central nervous system therapeutic molecule has to permeate for its activity. Finding the potent lead candidates capable of crossing the BBB remains to be a major challenge in neurodegenerative diseases. In the present review, attempts have been made to discuss on all these important aspects. Keywords: Alzheimer's disease, Amyloid precursor protein, Î²-amyloid, Blood-brain barrier, Flavonoids, Molecular docking, Multi-enzyme targeting. Â 